Long-term stability of Class II division 1 treatment with the MARA combined with fixed appliances - Fonçatti, Camilla Fiedler (2018)
Introduction: Successful treatment of class II Division 1 malocclusion is also implied to the long-term stability of treatment changes and many are the factors that can influence that. Objective: This research aimed to evaluate the long-term stability of the cephalometric changes obtained during Class II malocclusion correction with the MARA (Mandibular Anterior Repositioning Appliance) associated with fixed appliances. Methods: The treatment group comprised 12 patients who were evaluated at three stages: pretreatment (T1), posttreatment (T2) and long-term posttreatment (T3). The mean initial age of the patients was 12.35 years and the mean final age was 15.65 years. The mean age at the long-term posttreatment stage was 22.53 years and the mean long-term posttreatment period was 6.88 years. The control group comprised 12 subjects with normal occlusion and no orthodontic treatment with ages comparable to the treatment group at the posttreatment and long-term posttreatment stages. Intra-treatment group comparison between the three stages was performed with repeated measures analysis of variance (ANOVA), followed by Tukey tests. Intergroup comparison of posttreatment changes and normal growth changes of the treatment group were performed with t tests. Results: reduction of the maxillary protrusion and improvement of the maxillomandibular relationships remained stable during the long-term posttreatment period. Maxillary incisors inclination and overjet presented a tendency to relapse in relation to the control group Conclusions: Despite the different amount of growth potential, the reduction of the maxillary protrusion and maxillomandibular relationship improvement remained stable with no difference from normal occlusion behavior. Palatal inclination of the maxillary incisors and the overjet improvement showed a slight tendency towards relapse when compared to normal occlusion. Therefore, an increase of active retention time could be recommended to prevent that.